Role of Community Pharmacies in Rational use of Medicines: A Scenario in Pakistan - Aslam, Fahmida (Journal of Pharmacy Practice and Community Medicine)
According to FIP Global Pharmacy Workforce Report there are more than 80,000 pharmacies in Pakistan and 12000 pharmacists.[1] Whereas more than 708 pharmacists of Pakistan have departed abroad for their better future.[2] Only 10% of pharmacists are involved in community pharmacy practices. It means that 1130 pharmacists are available for more than 80,000 pharmacies. So 99.98 % pharmacies are working without pharmacists. If we include the services of pharmacy technicians which are about 40000 shows that almost half of pharmacies are without qualified persons.[1,3]